A PAREMIOLOGIST’S DREAM COME TRUE: “THE WOLFGANG MIEDER INTERNATIONAL PROVERB LIBRARY” AT THE UNIVERSITY OF VERMONT - Mieder, Wolfgang (Proverbium - Yearbook, 2020)
This is a report describing the events that resulted in the establishment of “The Wolfgang Mieder International Proverb Library” in May of 2019 at the University of Vermont. It is an account of Prof. Mieder’s donation of about 9000 proverb collections and studies about proverbs to his university. They are now housed in the historical Billings Library on campus. As a research center it welcomes scholars and students from anywhere to pursue their paremiographical and paremiological research projects. The report also includes a number of press releases that reported on this exciting matter. Several pictures of the beautiful bookcases appear at the end of these accounts.